Pirfenidone treatment in a patient with IPF and possible initial hypersensitivity pulmonitis - Cinetto, F.; Agostini, C. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
The diagnosis of idiopathic pulmonary fibrosis (IPF) requires exclusion of other known causes of interstitial lung disease (ILD) (e.g., domestic and occupational environmental exposures, systemic connective tissue disease, and drug toxicity), the presence of a ‘usual interstitial pneumonia’ (UIP) pattern on high resolution computed tomography (HRCT), and specific combinations of HRCT and histopathologic patterns in patients subjected to surgical lung biopsy (SLB). A clear diagnosis and early treatment with currently the only approved anti-fibrotic drug, pirfenidone, represents the standard of care for the treatment of mild-to-moderate IPF. This case report describes a patient with possible initial hypersensitivity pneumonitis and subsequent diagnosis of IPF with late development of pulmonary hypertension, and who was a candidate for lung transplantation. The patient showed slow progression of IPF during pirfenidone treatment in the CAPACITY and RECAP studies.